2021
DOI: 10.1111/coa.13735
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia and hyposalivation in patients with obstructive sleep apnoea

Abstract: Objective (a) To report the xerostomia prevalence and severity in patients with obstructive sleep apnoea (OSA). (b) To assess the saliva pH in patients with OSA. Design Simultaneous cohort observational clinical study. Setting In Sleep Medicine Centre at Lomonosov Moscow State University from March to June 2019. Participants The study was conducted on 30 patients with OSA aged from 35 to 65 years. Main outcomes measures The diagnosis of sleep apnoea was made after standard polysomnography using the Domino prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The average pH value in patients with mild, moderate, and severe apnea was 6.40 ± 0.017, 6.15 ± 0.27, and 5.87 ± 0.24, respectively. The acidity of the saliva was correlated with the level of OSA, and it is statistically increased with the increment of the OSA severity (Makeeva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The average pH value in patients with mild, moderate, and severe apnea was 6.40 ± 0.017, 6.15 ± 0.27, and 5.87 ± 0.24, respectively. The acidity of the saliva was correlated with the level of OSA, and it is statistically increased with the increment of the OSA severity (Makeeva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They further demonstrated that dry mouth upon awakening is a common symptom with OSA and 22 (73.3%) of the 30 patients evaluated had dry mouth and the prevalence of sleep-related xerostomia is correlated with OSA severity. In the majority of patients, dry mouth was correlated with mouth breathing and not salivary hypofunction and only 20% of the patients exhibited objective signs of hyposalivation [41].…”
Section: Oral-related Conditions Associated With Osamentioning
confidence: 91%
“…The alkalinity of saliva also increases with dysfunctions such as certain foodstuffs consumed, enzyme and secretion production of the pancreas, and liver problems. Although the disruptions of the pH balance to which the oral environment is exposed by the foods consumed can be limited by diet, saliva pH changes caused by the medications and diseases used by the patients cannot be prevented [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%